2012
DOI: 10.1002/jbm.a.34300
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of fluoride‐coated magnesium‐calcium alloys with optimized degradation kinetics in a subcutaneous mouse model

Abstract: The principle of biodegradation has been considered for many years in the development of cardiovascular stents, especially for patients with congenital heart defects. A variety of materials have been examined with regard to their suitability for cardiovascular devices. Iron- and magnesium-based stents were investigated intensively during the last years. It has been shown, that iron, or iron based alloys have slow degradation kinetics whereas magnesium-based systems exhibit rapid degradation rates. Recently we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 36 publications
1
30
1
Order By: Relevance
“…Manganese will be used as a supplement metal of the iron-based alloys with concentrations <10% (w/w). Soluble products of manganese decomposition (Mn 21 ) will be diluted in vivo to normal plasma concentrations, so that adverse systemic effects are unlikely. In a binary FeMn alloy, Mn is the minor alloying component (<10%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese will be used as a supplement metal of the iron-based alloys with concentrations <10% (w/w). Soluble products of manganese decomposition (Mn 21 ) will be diluted in vivo to normal plasma concentrations, so that adverse systemic effects are unlikely. In a binary FeMn alloy, Mn is the minor alloying component (<10%).…”
Section: Discussionmentioning
confidence: 99%
“…19 Fluoride coating has been shown to delay the degradation process; however, corrosion still occurs at undesirably rapid rates. 20,21 Although pure iron has been shown to exhibit excellent biocompatibility, 22 the corrosion rates are too slow to be suitable for pediatric cardiovascular devices.…”
Section: Introductionmentioning
confidence: 99%
“…Because fluoride is a natural anion within the skeleton, a good biocompatibility of this coating is expected, and this was demonstrated by Thomann et al [32] by implanting fluoride-coated MgCa alloy cylinders in the tibiae of rabbits, where new bone formation can be observed postimplantation. Likewise, Drynda et al [9] implanted cylindrical plates of MgCa alloys into the subcutaneous tissue of mice and did not report any relevant significant adverse effects caused by the fluoride-coated implants. These results are in line with our findings in this study.…”
Section: Alloy Composition and Coatingmentioning
confidence: 96%
“…Results indicated that Mg–Ca alloys had higher corrosion rates compared to WE43 and fluoride coating was a suitable way to reduce corrosion rate. However, no significant differences were observed in inflammation and capsule formation [26] .…”
Section: Progress On Mg-based Stentsmentioning
confidence: 99%